PERSEPSI PETUGAS KESEHATAN STAFF MANAJEMEN DAN DIREKTUR TENTANG KEBIJAKAN IMPLEMENTASI KAWASAN TANPA ROKOK DI RUMAH SAKIT UMUM DAERAH DELI SERDANG - Balqis Wasliati; Beni Satria; Harris Rambey; Delita Br Panjaitan; Raisha Octavariny; Christina Octavia P (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Hospital as a health centers which can be access with all of people is one of area which declared by smoke free area and director or person in charge of the places which declared by smoke free area has obligation to establish and make implementation of the smoke free area. That is a background of researcher to do a research which can give a knowledge and comprehension about perception of employees and visitors about the implementation smoke free area in General Hospital of Kabanjahe because they are the people who have an impact to implementation of regulation which declared in the hospital area. The research is a descriptive qualitative research. This study uses data collection techniques with in-depth interview for 9 informants.The result showed that both health care workers, management staff, directors strongly support the implementation of the smoking area in the house common areas serdang deli.However, implementation of the smoking area in public hospital serdang deli area is already running with the maximum, either aapeal the from of words ir in written rules in the persistence of the employees and visitors who smoke in several places in the district hospital deli serdang. Others outside the waiting room, in the parking lot and at the general hospital cafetaria serdang deli.